Knowledge and attitude towards antibiotic usage among patients attending UiTM Primary Care Clinic. / Dr Zati Sabrina Ahmad Zubaidi - Ahmad Zubaidi, Zati Sabrina (2018)
Antibiotic resistance is fast becoming a national as well as a global threat to the stability and survival of human kind. In Malaysia, we are beginning to observe resistance happening to the most powerful group of antibiotics available, the Carbapenems. Therefore, the WHO has encouraged research and development on antibiotic usage especially among the community to further understand and find an appropriate solution to improve the current situation. This study aims to explore the level of antibiotic knowledge and attitude appropriateness on antibiotic usage, identify the population with inappropriate attitude towards antibiotic usage and explore their associated factors and finally measure the prevalence of antibiotic self-medication among this study population. This cross-sectional study was conducted among 256 respondents attending UiTM Primary Care Clinic who fulfilled the inclusion and exclusion criteria. This study used a set of a validated and translated questionnaire which was designed in the Malaysian population to measure the respondents' knowledge and attitude towards antibiotic usage. It was found that the mean attitude score was 29.5 ±4.19 and up to 50% of the respondents had inappropriate attitude towards antibiotic usage while the mean score for knowledge was 5.94 ± 2.4 and 40% of the respondents had poor antibiotic knowledge. The highest incorrect knowledge was on the domain role of antibiotics and the highest inappropriate attitude response is expecting antibiotic from the doctor for symptoms of common colds. Among respondents with inappropriate attitude towards antibiotic, the highest in correct knowledge and inappropriate attitude response is similar to the general population however it was found to be more prevalent in this group of respondents. Finally, the prevalence of antibiotic self-medication in this population is 13.3%. Poor antibiotic knowledge and low education level were found to be the two associated factors to inappropriate attitude towards antibiotic usage. The prevalence of antibiotic selfmedication is low in this population compared to other developing countries (38.8%). This is potentially because the Malaysian health care system is heavily funded by the government. Therefore, purchasing antibiotics OTC is far more expensive. The findings of this study may help to facilitate clinicians to design a targeted antibiotic campaign. Nevertheless, the sampling method for this study was not random and it was conducted in one primary care centre. Therefore, it is pertinent for the results to be taken with caution.